Electrostatic mechanism of bromine release during ozone depletion events - Tkachenko, K. Yu. (Ukrainian Antarctic Journal, 2012)
In the investigation we discuss boundary layer ozone depletion events associated with spring and polar sea ice zone, special role of bromine in these processes and a viewpoint of author concerning mechanisms of bromine release in “fair weather” conditions and under high wind.